Immunoglobulin-E and Thyroid-Stimulating Hormone Receptor Antibody in Graves’ disease with Atopy - Wironegoro, Rio; Baskoro, Ari; Effendi, Chairul; Pranoto, Agung (Gaceta Médica de Caracas, 2021)
Background: Graves’ disease is known to have a high recurrence rate with recent evidence linked pollen allergy as one of the factors that might induce relapse in Graves’ disease. Therefore, it was argued that IgE might play a role in inducing relapse of Graves’ Disease. This study aims to investigate the correlation between IgE and Thyroid-Stimulating Hormone ReceptorAntibody (TRAb) in Graves’ disease respondents with a history of atopy.